Primeiros contributos para um estado da expressão e da compreensão na criança com base em provas de linguagem oral e escrita - Pinto, Maria da Graça Lisboa Castro (1985)
The oral and written language of 180 Portuguese children was examined from the points of view of expression and comprehension. As a basis of study two different types of analysis which had been furnished by A. Girolami-Bouli-nier as well as the methodology used by that authoress were adopted. The children in question carne from among three different age groups: the 8, 9 and 10 year olds (respective average ages). The objective of this study is to supply some information which will then permit an «appraisal», from a verbal point of view, of a given individual, thereby possibly throwing light upon certain cases of language disturbance.